Insufficient Expression of Cyclooxygenase-2 Protein Is Associated With Retarded Degradation of Aggregated Protein in Diabetic Glomeruli - Yasushi Hirasawa; Aiko Muramatsu; Yoshio Suzuki; Tadashi Nagamatsu (Elsevier, 2006)
To elucidate the involvement of cyclooxygenase (COX) in degradation of aggregated protein in diabetic glomeruli, we used streptozotocin (STZ)-induced diabetic mice and aggregated bovine serum albumin (a-BSA) as a model protein. There was a higher deposition of a-BSA in diabetic glomeruli compared to normal glomeruli 18 h after a-BSA injection at 4 and 8 weeks after STZ. Degradation of a-BSA was confirmed using isolated glomeruli. Diabetic glomeruli produced prostaglandin E2 (PGE2) more than normal glomeruli in the basal level at 8 weeks. a-BSA caused further increase of PGE2 production in normal glomeruli, but not in diabetic glomeruli. Niflimic acid, a selective COX-2 inhibitor, reduced PGE2 production of normal glomeruli in the a-BSA loading group, but not that in the control group. In diabetic glomeruli, niflimic acid reduced PGE2 production in both the control group and a-BSA loading group. In normal glomeruli, a-BSA increased expressions of both COX-2 mRNA and protein. However, in diabetic glomeruli, a-BSA increased COX-2 mRNA expression but not COX-2 protein expression. These results suggest that retarded degradation of aggregated protein in diabetic glomeruli is associated with lack of further expression of COX-2 protein and further production of PGE2 in response to aggregated protein. Keywords:: cyclooxygenase-2, aggregated bovine serum albumin, streptozotocin, diabetic, glomeruli